2021
DOI: 10.1152/jn.00471.2020
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent long-term potentiation of electrical synapses in the mammalian thalamus

Abstract: Activity-dependent changes of synapse strength have been extensively characterized at chemical synapses, but the relationship between physiological forms of activity and strength at electrical synapses remains poorly characterized and understood. For mammalian electrical synapses comprising hexamers of connexin36, physiological forms of neuronal activity in coupled pairs have thus far only been linked to long-term depression; activity that results in strengthening of electrical synapses has not yet been identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 110 publications
7
22
0
Order By: Relevance
“…Distances of dendritically located electrical synapses between cerebellar Golgi cells do not correlate with coupling strength measured between somas (Szoboszlay et al, 2016), indicating a possible compensation for distance by strength upregulation for those cells. Further, our previous work demonstrating activity-dependent plasticity showed that asymmetry changes systematically with unidirectional activity or ion flow across the gap junction (Fricker et al, 2021;Haas et al, 2011).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Distances of dendritically located electrical synapses between cerebellar Golgi cells do not correlate with coupling strength measured between somas (Szoboszlay et al, 2016), indicating a possible compensation for distance by strength upregulation for those cells. Further, our previous work demonstrating activity-dependent plasticity showed that asymmetry changes systematically with unidirectional activity or ion flow across the gap junction (Fricker et al, 2021;Haas et al, 2011).…”
Section: Discussionmentioning
confidence: 85%
“…Demonstrations of electrical synapse asymmetry are numerous throughout the mammalian brain, including retina (Veruki & Hartveit, 2002), cortex (Galarreta & Hestrin, 2002), inferior olive (Devor & Yarom, 2002), dorsal cochlear nucleus (Apostolides & Trussell, 2013), mesencephalic trigeminal nucleus (Curti et al, 2012), cerebellar Golgi cells (Dugué et al, 2009;Szoboszlay et al, 2016), and the thalamic reticular nucleus (TRN) (Haas et al, 2011;Sevetson & Haas, 2015;Zolnik & Connors, 2016). Recent results show that asymmetry can be modified during the activity that results in electrical synapse plasticity (Fricker et al, 2021;Haas et al, 2011), indicating that it is a dynamic property that is under activity-dependent regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study of this system has suggested the direction of compensation, i.e. potentiation or depression, depends on the degree of calcium influx elicited (Fricker et al, 2020). Activity dependent modulation of gap junctions has also been observed in the Retizius cells of Hirudo medicinalis (Welzel and Schuster, 2018).…”
Section: Figure 22 Electrical Synapse Potentiation (Eltp) Requires Desynchronized Activity and Camentioning
confidence: 98%
“…The past decade has yielded evidence suggestive of a voltage-dependent modulation of electrical synapses. The thalamic reticular nucleus (TRN) undergoes eLTD or eLTP following evoked bursting (Haas et al, 2011c) or spiking (Fricker et al, 2020). Evoked spiking has been shown to cause eLTP in Hirudo medicinalis as well (Welzel and Schuster, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation